2010
DOI: 10.1016/j.ejso.2010.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic lymph node ratio in stage III rectal cancer; prognostic significance in addition to the 7th edition of the TNM classification

Abstract: Aims: Optimal staging in rectal cancer is indispensable for the decision on further treatment and estimation of prognosis. This study assesses the prognostic capacity of the metastatic lymph node ratio (LNR) in addition to the new TNM classification.Methods: LNR was determined, in stage III patients from the Dutch TME trial. Six year median follow up data from the trial database were used to analyse the relation of LNR to overall survival (OS) and local recurrence (LR). The relation of LNR to lymph node yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…LN burden is dependent upon the extent of surgical resection and is also influenced by the extent of pathological scrutiny. The concept of LN burden or ratio has been studied in other cancers [60][61][62][63] including oral and cutaneous squamous cell carcinoma of the head and neck [64,65]. However, the prognostic impact of LN burden has not been well explored in thyroid cancer [27,29].…”
Section: Ln Burdenmentioning
confidence: 99%
“…LN burden is dependent upon the extent of surgical resection and is also influenced by the extent of pathological scrutiny. The concept of LN burden or ratio has been studied in other cancers [60][61][62][63] including oral and cutaneous squamous cell carcinoma of the head and neck [64,65]. However, the prognostic impact of LN burden has not been well explored in thyroid cancer [27,29].…”
Section: Ln Burdenmentioning
confidence: 99%
“…Less easy to explain, numerous articles underscore that the more LNs removed and examined, the better the outcome in patients, both with and without positive nodes. [1][2][3] However, questions arise as to what is the minimal number of LNs to examine in order not to miss any LN deposits. Three recent articles [4][5][6] have shed some (hued) light on these disconcerting questions.…”
mentioning
confidence: 99%
“…Increasing data today point to the number of lymph nodes (LNs) removed and examined as an important parameter in LN staging 1,2 : The more LNs gathered and examined, the greater the likelihood of identifying positive LNs. Less easy to explain, numerous articles underscore that the more LNs removed and examined, the better the outcome in patients, both with and without positive nodes.…”
mentioning
confidence: 99%
“…[4][5][6][7][8] Peng and colleagues 8 were the first to demonstrate the association between LNR and survival rate in patients with rectal cancer. The mean LNR was 0.34, and they reported that LNR was an independent risk factor for local recurrence, DFS and OS.…”
mentioning
confidence: 99%
“…The mean LNR was 0.34, and they reported that LNR was an independent risk factor for local recurrence, DFS and OS. In these studies, [4][5][6][7][8] 9 According to the seventh edition of the TNM classification, patients with stage III cancer are classified based on the number of positive nodes. Intuitively, it seems safe to believe that the prognostic significance of 5 positive nodes out of a total of 5 will be completely different from 5 positive nodes out of a total of 30.…”
mentioning
confidence: 99%